1982
DOI: 10.1038/icb.1982.17
|View full text |Cite
|
Sign up to set email alerts
|

METABOLISM OF BABESIA PARASITES IN VITRO. COMPARISON OF SEVERAL ZWITTERION BUFFERS FOR THE IN VITRO INCUBATION OF BARESIA RODHAINI

Abstract: Summary. The effect on the haemoprotozoan parasite Babesia rodhaini of adding a zwiiterion buffer, HEPES. to a basal medium was studied by comparing the glucose uptake, ATP concentration, medium pH and infectivity of parasitized rat erythrocytes every 4 h during 24 h incubalion in either Krebs Ringer phosphate (KRP) or KRP plus 28 mM HEPES. KRP plus HEPES was found to be superior to KRP for the maintenance of glucose uptake, erythrocyte ATP concentration, medium pH ynd infectivity of the parasite.Having establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The most likely one is that the use of 40 mM TES buffer during 4 h incubation provided a much more favourable environment for metabolic activity by the parasites than did 28 mM TES used during 18 h incubation. Barry (1982b) showed that 40 mM TES improved the survival rate of B. rodhaini up to 10-fold compared to 28 mM TES during 18 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely one is that the use of 40 mM TES buffer during 4 h incubation provided a much more favourable environment for metabolic activity by the parasites than did 28 mM TES used during 18 h incubation. Barry (1982b) showed that 40 mM TES improved the survival rate of B. rodhaini up to 10-fold compared to 28 mM TES during 18 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…In the 4 and 18 h incubation experiments in which individual amino acids were estimated, the medium was supplemented with 40 and 28 mM tris (hydroxymethyl) methylamino ethane sulphonic acid (TES), respectively, to increase buffering capacity (Barry, 1982b).…”
Section: Preparation and Incubation Of Erythrocyte Suspensionsmentioning
confidence: 99%